Identifikasi Kerusakan dan Perbaikan Refrigerator Freezer AR763 - Laura Nisa Tilqadri; Ikhwan Nofitra; Isnanda; Feidihal; Yuli Yetri (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2021)
With the rapid development of technology today the refrigerator freezer (refrigerator) as a tool to help us in storing food for long lasting. Refrigeration is a process of absorption of heat from a substance or product so that the temperature is below the ambient temperature whereas, refrigerant is a substance used as a working fluid in the heat absorption process. It is this substance that circulates in the refrigeration machine, which absorbs heat from the object or air that is cooled, then dumps it into the surrounding air outside the object or room that is cooled. In the use of refrigenerator often experience damage, so it is necessary to analyze the damage. The analysis showed that there was damage to the AR 763 refrigerator freezer, namely the cooling system was blocked due to the refrigerator not operating (damaged) and causing the refrigerant in the system to freeze which caused the system to not work. Furthermore, the filter must be replaced because the filter holds a lot of dirt and there are damaged electrical components such as thermo fuse and timers due to the lifetime of the componen